Evaluasi Kebijakan Bus Trans Semarang pada Koridor I – Koridor VII - Nisriena Rachmi Putri; Mohammad Muktiali (Jurusan Perencanaan Wilayah dan Kota, 2021)
In 2009, Semarang added a public transportation mode, the Trans Semarang Bus, which is a manifestation of the implementation of public transportation policies in Semarang. The research object to be discussed in this study is the policy of the Trans Semarang Bus which focuses on corridors I - corridor VII. The main problem of the research is that the Trans Semarang Bus policy has not been optimized. In fact, the number of passengers only fulfilled 76.99% of the target in Corridor I - Corridor VII. The purpose of evaluation of the Trans Semarang Bus policy is to look for the best and worst indicators, criteria and corridors of the Trans Semarang Bus policy implementation. The method is quantitative with AHP and scoring analysis techniques using 4 indicators namely Input, Process, Output and Outcome, also 6 criteria namely Effectiveness, Efficiency, Adequacy, Equity, Responsiveness and Accuracy which will be ranked by 4 experts. The result, Input indicator is ranked first, and the last is Output. The criteria that have the highest accumulative score is Justice, while the lowest is Sufficiency. The corridor which has the highest accumulative score of all indicators is Corridor I, while the lowest is Corridor VII.